COMMON ERRORS IN COMPOSITION WRITING BY COLLEGE STUDENTS - Gianinna Elaine Malapote Labicane; Ricky Michael Morales Oliva (Universitas Islam Sumatera Utara (UISU), 2022)
The alarming decline in the English language proficiency of Filipinos in recent years calls for further exploration into the challenges encountered by learners across the four macro-skills, particularly in writing, being the macro-skill met with the most challenge alongside speaking. Hence, this study aimed to identify the common writing errors of college students from the Marinduque State College in writing recount text and attempt to determine the reasons behind these writing deficiencies. Twenty (20) recount texts written by third-year Social Work for their World Literature course were subjected to analysis. The results revealed that punctuation use, selection of correct verbs and prepositions, capitalization, subject-verb agreement, and selection of appropriate pronouns were the areas in writing that the participants were most challenged with. These composition errors may be attributed to a lack of focus on grammatical rules in L2 learning and the strong influence of the native language. Hence, intervention on these identified writing deficiencies must be implemented immediately in order for the learners’ communicative writing skills to be at par with global standards for English communicative competency.